Preseving Batik Based on Buying Intention, Concern on the Environment and Self-Expressive Benefits - Ramadi, Nadya; Agustini, M.Y. Dwi Hayu (Celt: A Journal of Culture, English Language Teaching & Literature, 2022)
Batik reaches its international popularity since it is awarded as the Indonesian cultural heritage. Batik craftsmen innitiate to produce natural dyed batik as the response to the envionmental issues resulted to batik production. Consumers’ intention on green product has been increasing along the time. They are willing to pay higher price for green product since they can get psychological benefits in expressing their green orientation. Such consumers usually show awareness and show concern toward the environment. The study aims to analyze concern toward the environment, self-expressive benefits, and intention to buy green product of natural dyed batik Siputri as the approach to determine ways in preserving batik. Survey using questionnaire was conducted to the customers of batik Siputri. The questionnaire was distributed using Google form and the data was analyzed using descriptive supported by linier regression. The result indicates that intention to buy Siputri’s batik is influenced by self-expressive benefits and concern toward the environment. The management of Siputri must innovate the product and do marketing communication intended to leverage customers self-expressive benefits and increase positive attitude toward the environment.